2018
DOI: 10.3892/ol.2018.8491
|View full text |Cite
|
Sign up to set email alerts
|

XAV939 inhibits the proliferation and migration of lung adenocarcinoma A549 cells through the WNT pathway

Abstract: The present study assessed the effects of the tankyrase (TNKS) small molecule inhibitor XAV939 on the proliferation and migration of lung adenocarcinoma A549 cells and the possible underlying mechanism. To do this, the association between TNKS and the WNT/β-catenin signaling pathway in lung acinar adenocarcinoma was investigated. Immunohistochemistry was performed, which demonstrated that TNKS, β-catenin and Myc proto-oncogene protein (c-Myc) proteins are positively expressed in lung adenocarcinoma tissue; thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…18 Previous studies have shown that cisplatin could show efficacy in a variety of solid tumors, for example, ovarian cancer, 19 prostate cancer, testicular cancer 20 and lung cancer. 21 In our study, cisplatin was found to reduce the activities of LADC, A549 and H23 cells, and the expression of GOLPH3 was also significantly reduced. To further investigate the role of GOLPH3 in anticancer effect of cisplatin, knocking out or overexpressing the GOLPH3 plasmid into A549 and H23 cells showed that silencing GOLPH3 could further inhibit cell viability, compared to cisplatin-treated cancer cells, and that the phosphorylation level of Akt protein was significantly reduced.…”
Section: Discussionsupporting
confidence: 54%
“…18 Previous studies have shown that cisplatin could show efficacy in a variety of solid tumors, for example, ovarian cancer, 19 prostate cancer, testicular cancer 20 and lung cancer. 21 In our study, cisplatin was found to reduce the activities of LADC, A549 and H23 cells, and the expression of GOLPH3 was also significantly reduced. To further investigate the role of GOLPH3 in anticancer effect of cisplatin, knocking out or overexpressing the GOLPH3 plasmid into A549 and H23 cells showed that silencing GOLPH3 could further inhibit cell viability, compared to cisplatin-treated cancer cells, and that the phosphorylation level of Akt protein was significantly reduced.…”
Section: Discussionsupporting
confidence: 54%
“…33 XAV939 is a selective small-molecule inhibitor of Wnt/β-catenin signaling. 34 In addition, the in vitro cell cultures indicated that XAV939 and sitagliptin intervention inhibit high glucoseinduced hyperexpression of Wnt4 and β-catenin, downregulate α-SMA expression, and partially restore E-cadherin biological activity. Our in vivo studies also demonstrated that sitagliptin can ameliorate renal functional and structural damage by reducing the hyperexpression of Wnt4 and β-catenin and inhibiting transdifferentiation in the tubulointerstitium.…”
Section: Discussionmentioning
confidence: 96%
“…We treated A549 cells (1,2,4,8,16,32,64, and 128 M), M2-like TAMs (1, 2, 4, 5, and 8 M), and ex vivo TAMs from human and mouse lung tumors with XAV939 (5 M; Tocris, Wiesbaden-Nordenstadt, Germany) and M2-like TAMs with RS 504393 (5 M; Tocris, Wiesbaden-Nordenstadt, Germany) as per the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay protocol and a previous study (40) for 24 hours at 37°C.…”
Section: Treatment With Xav939mentioning
confidence: 99%